Monoclonal Antibodies Targeting IL-5 or IL-5Rα in Eosinophilic Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis - Zhang, Chuchu; Wang, Yalei; Zhang, Meng; Su, Xiaojie; Lei, Ting; Yu, Haichuan; Liu, Jian (Frontiers in Pharmacology, 2021)
Background Although the predominant airway inflammation in chronic obstructive pulmonary disease (COPD) is neutrophilic, approximately 20-40% of COPD patients present with eosinophilic airway inflammation. Compared with non-eosinophilic COPD patients, eosinophilic COPD patients are characterized by a greater number of total exacerbations and higher hospitalization rates. Furthermore, anti-interleukin-5 (IL-5) therapy, consisting of monoclonal antibodies (mAbs) targeting IL-5 or IL-5 receptor ɑ (IL-5Rɑ), has been proven to be effective in severe eosinophilic asthma. This meta-analysis aimed to determine the efficacy and safety of anti-IL-5 therapy in eosinophilic COPD. Methods We searched the PubMed, Web of Science, Embase, and Cochrane Library databases from inception to August 2020 (updated in June 2021) to identify studies comparing anti-IL-5 therapy (including mepolizumab, benralizumab, and reslizumab) with placebo in eosinophilic COPD patients. Results Anti-IL-5 therapy was associated with a decrease in acute exacerbation rate (RR 0.89; 95% CI 0.84 to 0.95, I2 = 0%), and the severe adverse events (RR 0.90; 95% CI 0.84 to 0.97, I2 = 0%). However, no significant improvement was observed in pre-bronchodilator forced expiratory volume in 1 s (FEV1) (WMD 0.01; 95% CI -0.01 to 0.03, I2 = 25.9%), SGRQ score (WMD -1.17; 95% CI -2.05 to -0.29, I2= 0%), and hospital admission rate (RR 0.91; 95% CI 0.78 to 1.07, I2 = 20.8%). Conclusion Anti-IL-5 therapy significantly reduced the annual acute exacerbation rate and severe adverse events in eosinophilic COPD patients. However, it did not improve lung function, quality of life, and hospitalization rate.